Benchmarking Study "Strengthening Savings and Loan Business" East Java Province Small & Medium Enterprises Cooperative Office and Sumber Sejahtera Credit Union Cooperative Together with the South Kalimantan Provincial Office of Cooperatives and Small & Medium Enterprises - Isra Ul Huda; Noor Ritawaty; Sutrisno Sutrisno (Mandalika Journal of Community Services, 2025)
This research presents a Benchmarking Study aimed at strengthening the "Simpan Pinjam" (Savings and Loan) operations in cooperatives, specifically focusing on Dinas Koperasi Usaha Small & Medium Enterprises in East Java and Credit Union Sumber Sejahtera in South Kalimantan. The study was conducted with the intention of improving the performance and sustainability of cooperative-based financial institutions through benchmarking best practices. By comparing operational models, strategies, and challenges faced by different regions, the study identifies key areas for development. Key objectives include enhancing financial literacy among cooperative members, promoting better management practices, and ensuring long-term financial sustainability. A collaborative approach was employed, with extensive input from government agencies and cooperative leaders, aiming to create a replicable model for the strengthening of cooperatives across Indonesia. The findings and recommendations from this study will provide crucial insights for policymakers and cooperative managers to implement more effective business strategies, ultimately contributing to the economic empowerment of local communities.